José Leonard y Enrique Guzmán: Controversias por el librepensamiento y el establecimiento de la logia masónica “Progreso n° 41” en Granada, Nicaragua (1881-1883) - Valdés Valle, Roberto Armando (2015)
The article analyzes some of the diary entries of the Nicaraguan writer Enrique Guzman referring to the educational and Masonic institutions that Joseph Leonard (Polish citizen) developed in the cities of Leon and Granada between 1881 and 1883. In these brief notes is reconstructed the controversies that generated radical ideas (freethinking) of Leonard among conservative Catholic Nicaraguan sectors, but also the process by which Leonard settled in Granada lodge “Progress No. 41”. It also reveals the reasons that compelled Leonard to migrate to El Salvador, which were connected with the establishment of this lodge. Finally, it the article is meant to clarify what was the political ideology of Guzman in that moment of his intellectual career, as well as the possibility of whether or not he was a Mason.